Patient journey in cystinosis: focus on non-adherence and disease management - Gema Ariceta; Simón Lalanza; Catalina Peña; Marta Martínez Montero; Carlos Bezos Daleske; Laura Acuña Álvarez; Elisa Giner (BioExcel Publishing Ltd, 2024)
Background: Few studies have assessed patient-reported experience measures in nephropathic cystinosis. This study uses patient reports focused on the impact of cystinosis, cysteamine treatment-associated problems, and therapeutic adherence and suggests potential actions for improvement. Methods: In March 2022, six patients with nephropathic cystinosis treated with cysteamine, aged between 12 and 40 years as well as two caregivers, underwent standardized online interviews. Further, in April 2022, two online workshops were organized, each one with the participation of an advisory board consisting of up to four patients and six caregivers. As a result, the first patient journey mapping was developed considering pre-diagnosis, diagnosis and post-diagnosis steps, prescription of treatment, laboratory tests and daily life for patients, categorized by age (children, teenagers, adults). A patient support programme was also considered. Results: Patients were not completely aware of the risks associated with non-adherence. The main factors explaining poor adherence were impaired sleep and chronic fatigue, both related to cysteamine night dosing and prominent gastrointestinal symptoms. These factors have a negative impact on the daily lives of patients. Opportunities for improvement in disease management and therapeutic adherence in nephropathic cystinosis were highlighted. Consequently, a series of lines of action and suggestions were made. Conclusion: This qualitative study offers insights on nephropathic cystinosis from the point of view of patients and parents/caregivers. The critical steps during patient journey and the pitfalls for therapeutic adherence have been highlighted, opening ways to improve not only disease management but also the quality of life of patients with cystinosis. A lay summary is provided as supplementary material; available at: https://www.drugsincontext.com/wp-content/uploads/2024/10/dic.2024-7-1-Suppl-Lay-Summary.pdf